Study of growth and development in children with recurrent wheezing - Amin, Kunalkumar M.; Suman, Chandankumar (International Journal of Contemporary Pediatrics, 2025)
Background: Recurrent wheezing in early childhood may impact growth and development, yet comprehensive data on these associations remains limited. Objectives were to evaluate growth and developmental patterns in children with recurrent wheezing over a 12-month period. Methods: This prospective observational study included 150 children aged 6 months to 5 years with recurrent wheezing treated at GMERS Godhra. Anthropometric measurements, developmental screening, and wheezing severity assessment were performed at regular intervals. Growth parameters were analyzed using WHO standards, and development was assessed using the Denver developmental screening test II (DDST II). Results: Of 150 enrolled children (mean age 28.4±14.2 months), 142 completed follow up. Children with severe wheezing showed significantly lower growth velocity (7.1±1.4 cm/year) compared to mild wheezing (8.2±1.8 cm/year, p=0.028). Multiple regression analysis revealed significant associations between growth velocity and wheezing frequency (β=-0.284, p=0.001), ICS use (β=-0.186, p=0.008), and nutritional status (β=0.226, p=0.002). Developmental assessment showed normal progression in 85.9-90.1% across domains, with language delays being most prevalent (9.9%). Conclusions: Recurrent wheezing severity significantly impacts growth velocity in young children, while most maintain normal development. Regular monitoring of growth and development is essential in this population.